2016
DOI: 10.3889/oamjms.2016.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hormone Replacement Therapy on Insulin Resistance in Postmenopausal Diabetic Women

Abstract: BACKGROUND:Insulin resistance (IR) is closely associated with diabetes mellitus. On the other hand, increased visceral fat in menopause is also associated with IR, which makes postmenopausal diabetic women in a big risk for cardiovascular diseases. There are conflicting reports about the effects on hormone replacement therapy (HRT) on IR.AIM:The aim of the study was to investigate the effects of HRT on IR.METHODS:A total of 40 postmenopausal women with type 2 diabetes were enrolled and followed for 12 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 53 publications
0
24
0
1
Order By: Relevance
“…Furthermore, there are conflicting reports about the effects of hormone replacement therapy on insulin sensitivity. For instance, estrogen replacement therapy has been reported to have no effect on insulin sensitivity in post-menopausal women [29, 30], but it increased insulin sensitivity when administered in post-menopausal women with diabetes [31]. In addition, the association of sex hormones (testosterone and estrogen) with insulin resistance differs depending on the estrogen status [32].…”
Section: Testosterone and Diabetesmentioning
confidence: 99%
“…Furthermore, there are conflicting reports about the effects of hormone replacement therapy on insulin sensitivity. For instance, estrogen replacement therapy has been reported to have no effect on insulin sensitivity in post-menopausal women [29, 30], but it increased insulin sensitivity when administered in post-menopausal women with diabetes [31]. In addition, the association of sex hormones (testosterone and estrogen) with insulin resistance differs depending on the estrogen status [32].…”
Section: Testosterone and Diabetesmentioning
confidence: 99%
“…The effect of HRT on glucose homeostasis remains questionable [158]. A systematic review which included 16 trials with 17,971 postmenopausal women with type 2 DM demonstrated that estrogen replacement diminishes DM incidence and improves glycemic control [169], but there is no consensus yet.…”
Section: Introductionmentioning
confidence: 99%
“…20 Sejalan dengan studi intervensi bahwa pemberian Hormon Replacement Therapy (HRT) pada wanita postmenopause dapat memperbaiki sensitivitas insulin. 21 Selain itu, estrogen dapat menstimulasi proliferasi sel β sehingga meningkatkan sintesis insulin dan memiliki efek insulinotropik yang dapat merangsang pelepasa insulin postpandrial. 22 Asupan vitamin D menunjukkan tidak terdapatnya hubungan signifikan dengan kadar glukosa darah puasa sejalan dengan penelitian kohort yang dilakukan di Jepang.…”
Section: Hasil Karakteristik Subjekunclassified